THE ACTUAL TICK-BORNE INFECTIONS IN THE PERIOD OF COVID-19 PANDEMIC IN KEMEROVO REGION – KUZBASS - Хохлова, Зинаида Александровна; Медведева, Нина Владимировна; Середа, Татьяна Васильевна; Жилина, Наталья Михайловна; Спирина, Юлия Михайловна; Ботвиньева, Ирина Анатольевна; Батаева, Марина Евгеньевна (Medicine in Kuzbass, 2024)
The aim – the analysis of COVID-19 pandemic impact on clinical and epidemiological tick-borne infections indicators and assessment of information value of laboratory diagnostic methods for diagnosis verification.The materials and methods. Accounting and reporting documentation and laboratory data of FBUZ «Hygiene and epidemiology center in Kemerovo region – Kuzbass» in the period of 2019-2023. The ticks (Ixodes persulcatus), removed from the patients, patients, plasma, blood serum, cerebrospinal fluid were tested by RT-PCR test and immunoenzymatic analysis in the laboratory of the GBUZ Municipal Clinical Infectious diseases Hospital in the period of 2021-2023. Non-parametric Friedman and Wilcoxon tests, Kendall tau and Spearman correlation have been used in statistical material treatment in package of IBM SPSS Statistics-22.The results. The negotiability about tick bites has increased in the period of COVID-19 pandemic in Kemerovo region and Novokuznetsk. The borrelia contagiousness of the ticks is registered very rarely. The tick-borne encephalitis and tick-borne borreliosis morbidity has decreased. The rate of focal forms and mortality in tick-borne encephalitis have increased. There has been demonstrated an inverse relationship between indices of negotiability and the tick-borne encephalitis and tick-borne borreliosis morbidity. The tick-borne encephalitis and tick-borne borreliosis agents contagiousness rate of the ticks was higher in the first post-pandemic year. The DNA of the tick-borne borreliosis agent in 30,5 %, the monocytic erlichiosis of man in 8,2 %, HGA – in 9,5 %, RNA of the tick-borne encephalitis – in 2,9 % were tested by PCR test of ticks, removed from the patients. The monoinfection being registered in 94,2 % of ticks. The antibodies of class M to the tick-borne encephalitis were tested in 15 %, to the tick-borne borreliosis – in 28,7 % of blood serum sample test. And this made it possible to verify the diagnosis.The conclusion. The detected changes of clinical and epidemiological tick-borne infections indicators under investigation in the period of COVID-19 pandemic may be conditioned by influence of restrictive measures and changing the focus to COVID-19. The investigation of the ticks, removed from the patients, by PCR test was highly informative and essential for prevention activities. The immunoenzymatic analysis has the leading importance for the tick-borne encephalitis and tick-borne borreliosis diagnostics.
Keywords: tick-borne encephalitis; tick-borne borreliosis; negotiability; morbidity; clinical forms; contagiousness; PCR; immunoenzymatic analysis